37. IMPACT OF THE COVID-19 PANDEMIC ON THE TREATMENT PLAN FOR LUNG CANCER PATIENTS AT K HOSPITAL - TAN TRIEU FACILITY IN 2021 (Vietnam Journal of Community Medicine, 2024)
Background: Hospital K is an oncology hospital that received the most attention during the quarantine period because of the possibility of COVID-19 infection and its effects on the treatment plan of cancer patients. This study aims to describe the impact of the COVID-19 pandemic on the treatment plan for lung cancer patients at K Hospital - Tan Trieu facility.Method: A cross-sectional study on 110 lung cancer patients isolated at K Hospital - Tan Trieu facility during the blockade from May 7, 2021 to June 14, 2021. Collect information from research subjects' medical records.Results: Non-small cell lung cancer accounts for the highest rate (76.4%). The cancer stage recorded was mainly stage IV (61.8%). 97.3% of subjects had treatment regimens. At the time of quarantine, 33 patients were scheduled for surgery but 2 cases had not yet been performed; of the 30 patients who were prescribed radiotherapy, 9 patients received the full dose of radiation; of the 72 cases where chemotherapy was indicated, only 14 cases had completed the full cycle. At the time after medical isolation, after 3 months of treatment, 50 cases were stable, accounting for 51.5%, 26 cases died due to disease progression, accounting for 26%, and 7 cases progressed, accounting for 7.2%, 10 cases treated symptomatically (10.3%) and 2 cases refused treatment without evaluating treatment response.Conclusion: The COVID-19 pandemic has changed the treatment plan and affected the treatment outcomes of lung cancer patients at K Hospital - Tan Trieu facility.
Keywords: Prevention measures; COVID-19; directive documents; treatment plans; K Hospital - Tan Trieu facility